Impact of Insulin Resistance in Acne Vulgaris and Hirsutism Patients: An Analytical Cross-Sectional Study - Mohamed Tarek Elshawaf, Yasir Aljoudi, Ali Riaz, Feroza Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study's goals are to identify a causal connection between insulin resistance (IR) and hirsutism and acne vulgaris, as well as to evaluate the severity of the two conditions in relation to rising IR. Study design: An analytical cross-sectional study Place and Duration: This study was conducted at Primary Health Care Corporation, Qatar from August 2021 to August 2022. Methodology: In a predetermined proforma, a patient's entire clinical history as well as required variables, such as height, weight, body mass index (BMI), etc., were recorded in order to establish a link between IR and acne with/without hirsutism and only hirsutism.A HOMA-IR value of more than 2.5 was regarded as important and indicative of IR. Global Acne Grading System (GAGS) was used to determine the degree of acne, and the Modified Ferriman Gallwey Score was used to determine the severity of hirsutism (mFG). Results: The 354 participants in our study were divided into three groups: There was a statistically significant connection between IR and the severity and recurrence of acne in the Acne-only (N = 310) group. The homeostatic model assessment for insulin resistance (HOMA-IR), the modified Ferriman-Gallwey score, and recurrence were substantially correlated in the hirsutism-only (N = 26) group, demonstrating that insulin resistance increased with hirsutism severity and recurrence. In the sample of 18 people with acne and hirsutism (N = 18), higher BMI was positively linked with IR but not with the severity of both disorders. Conclusion: Causing serious, resistant acne and hirsutism, IR has come to be recognized as a significant contributory, if not causal, event. The mental stress affected by these conditions is greatly impacted, requiring a different approach to case management. Keywords: Acne, Hirsutism, Dermatology practice, Psoriasis, PCOS, Insulin resistance